PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA DOSEN TETAP DI SEKOLAH TINGGI PARIWISATA BALI INTERNASIONAL DENPASAR - Ni Made Christina Gariyasa; Made Yudi Darmita (Universitas Triatma Mulya, 2021)
The academic quality of a tertiary institution cannot be separated from its success in organizing the Tri Dharma of Higher Education, namely Education, Research and Community Service. Higher Education is required to continuously develop three advantages, namely excellence in education, research and community service related to the utilization and application of science, technology, and art (IPTEKS). This study aims to analyze the effect of motivation and competence on the performance of permanent lecturers. The number of samples in this study were 63 respondents. Data collection techniques in this study are questionnaires and documentation. Sampling uses a census technique, which is a sampling technique that is carried out on certain objectives and considerations. The research method used in this study is a quantitative method. In the analysis of multiple linear regression obtained equation is Y = 4.048 + 0.204X1 + 0.238X2. In addition to this it is also proven that the influence of Motivation on the Performance of Permanent Lecturers at the Bali International Tourism College is a positive and significant effect, as evidenced by the existence of a probability value of less than 0.05 which is 0.04. While the influence of Competence on the Performance of Permanent Lecturers at the Bali International School of Tourism showed a positive and significant effect, as evidenced by the existence of a probability value smaller than 0.05 which is 0.008. For the influence of motivation and competence on the performance of permanent lecturers at the Bali International Tourism College is 39.9%.